Studi Numerik Pengaruh Geometri Tube dan Variasi Baffle terhadap Perpindahan Kalor pada Heat Exchanger Tipe Shell and Tube - Eko Wahyu Saputro; Agus Jamaldi (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to numerically investigate the effect of tube geometry and baffle variation on heat transfer performance in a shell-and-tube heat exchanger. The model employed a honeycomb tube geometry with baffle height variations of 65%, 75%, and 85%. Numerical simulations were conducted using ANSYS Fluent 2024 R2 with mass flow rates ranging from 0.25 to 1 kg/s. The analyzed parameters included outlet temperatures of hot and cold fluids, heat flow, and flow distribution visualized through contour and streamline plots. The results show that increasing mass flow rate leads to a higher heat flow rate but reduces the hot fluid outlet temperature due to shorter contact time. Baffle variation significantly affected performance, with the 85% baffle height producing more turbulent flow and the highest heat flow, reaching 14.89 kW at 1 kg/s. Furthermore, the comparison of tube geometries revealed that oval tubes outperformed honeycomb tubes, achieving a heat flow of up to 40.55 kW under the same conditions. Although the results of this study are less optimal compared to previous research, it still provides a valuable contribution to the selection of tube geometry types and baffle heights in shell-and-tube heat exchangers.